Working conditions and work performance of Iloilo City government employees - Bautista, Ma. Jonalyn; Jalandoni, Liza Glo-Anne; Licera, Sarah Jane; Osano, Maria Pamela; Solidarios, Greta
The study investigates the working conditions at the City Hall in Robinson's Place Iloilo and how they affect the work performance of the City Government employees. It also establishes the relationship between working conditions and work performance and determines measures to ensure good working conditions in Iloilo City Hall to enhance the work performance of its employees. four offices of the City Hall were studied involving 18 respondents selected through convenience sampling. from each of the four offices, a total of three respondents from Finance Department, four from Assessor, eight from Budget, and seven from the accounting department were taken who willingly answered the questionnaires. working conditions and work performance were the units of analysis that involved descriptive statistic. Descriptive analysis and evaluation were made in working conditions related to work performance of the employees. Findings of the study revealed that City Government do not have any choice after the building in Plaza Libertad have been declared by the City Engineer's Office as unsafe and dilapidated. It was a good choice for the relocation because of its accessibility and convenience to the public and good ventilation. However, since the Iloilo City Government office is located inside a mall, the site can be noisy, with so many distractions. The individual offices are not properly arranged in each department creating an atmosphere of disarray and confusion. Absence of cubicles is also a problem making it appear congested and disorderly.